High-quality Momordica balsamina genome elucidates its potential use in improving stress resilience and therapeutic properties of bitter gourd - Vinay, N. D.; Singh, Kalpana; Ellur, Ranjith Kumar; Chinnusamy, Viswanathan; Jaiswal, Sarika; Iquebal, Mir Asif; Munshi, Anilabha Das; Matsumura, Hideo; Boopalakrishnan, G.; Jat, Gograj Singh; Kole, Chittaranjan; Gaikwad, Ambika Baladev; et al. (Frontiers in Plant Science, 2024)
Momordica balsamina is the closest wild species that can be crossed with an important fruit vegetable crop, Momordica charantia, has immense medicinal value and placed under II subclass of primary gene pool of bitter gourd. M. balsamina is tolerant to major biotic and abiotic stresses. Genome characterization of Momordica balsamina as a wild relative of bitter gourd will contribute to the knowledge of the gene pool available for improvement in bitter gourd. There is potential to transfer gene/s related to biotic resistance and medicinal importance from M. balsamina to M. charantia to produce high quality, better yielding and stress tolerant bitter gourd genotypes. The present study provides the first and high-quality chromosome-level genome assembly of M. balsamina with size 384.90 Mb and N50 30.96 Mb using sequence data from 10x Genomics, Nanopore and Hi-C platforms. A total of 6,32,098 TEs, 2,15,379 SSRs, 5,67,483 TF binding sites, 3,376 noncoding RNA genes, and 41,652 protein-coding genes were identified and 4,347 disease resistance, 67 heat stress related, 05 carotenoid related, 15 salt stress related, 229 cucurbitacin related, 19 terpenes related, 37 antioxidant activity, and 06 sex determination related genes were characterized. Genome sequencing of M. balsamina will facilitate interspecific introgression of desirable traits. This information is catalogued in the form of webgenomic resource available at http://webtom.cabgrid.res.in/mbger/. Our finding of comparative genome analysis will be useful to get insights into the patterns and processes associated with genome evolution and to uncover functional regions of cucurbit genomes.